Pembentukan Karakter Siswa melalui Pembiasaan dan Keteladanan Guru - Reksamunandar, Rhyan Prayuddy; Hadirman, Hadirman (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
The formation of student character through habituation and example can be the basic capital for character building in Islamic educational institutions. With this habituation and example, students get real examples where they study. This study aims to describe the character formation of students through habituation and example of teachers at MIN 1 Minahasa. This study used descriptive qualitative method. The results showed that the formation of student character through habituation at MIN 1 Minahasa was carried out by habituation in carrying out the dhuha prayer, greeting parents, teachers, older siblings, and peers. Students are accustomed to wearing uniforms, memorizing short verses and Asmaul Husna, the attributes of Allah, and getting used to reading prayers before and after the lesson begins and ends. Meanwhile, character building through the example of teachers is carried out by providing advice related to character education during the implementation of the morning apple, the learning process, and students’ daily activities at school.